Relationship between Ideal clinic status determination and measures of PHC performance, utilisation and expenditure per PHC facility headcount - Van Rensburg, Caitlin (Division of Medical Physics, 2025)
A well-functioning, high-quality primary health care (PHC) system will be essential to achieve the ambitious goals set forth in South Africa's proposed system of National Health Insurance (NHI). NHI, informed by principles of Universal Health Coverage, will introduce a centralised health financing scheme in a bid to improve equity in the current two-tiered (public/private) system of health care delivery. NHI will rely heavily on PHC facilities as the ‘gateway' to the health system. Against this backdrop and the findings of a 2012 facilities audit report which revealed less than 50% of South Africa's public health facilities at the time complied with vital measures for health care delivery, the Ideal Clinic Realisation and Maintenance Programme (ICRMP) was developed as a tool for quality improvement. The ICRMP encompasses a comprehensive framework of standards which primary care facilities should meet, with manuals and training provided for facility staff alongside district support to assist facilities in doing so. Under the ICRMP, clinics are routinely assessed and afforded the status of an ‘Ideal Clinic' if specified minimum scores are met. These assessments should be accompanied by measures to improve areas of the framework under which clinics scored poorly. Facility managers should be supported by a Perfect Permanent Team for Ideal Clinic Realisation and Maintenance (PPTICRM) established at district level to conduct peer reviews and to improve on clinic weaknesses. National implementation of the ICRMP began in 2015/16, although the Western Cape joined only in 2016/17. While assessment/accreditation frameworks are increasingly being utilised globally as tools for quality improvement (as the ICRMP purports to be), evidence in support of their efficacy in achieving their stated goals remains sparse. Literature on the ICRMP is equally limited. Empirical studies considering the impact of early implementation of the ICRMP on indicators of primary care quality have yielded mixed results, suggesting minimal meaningful impact of the programme on patient waiting times, patient perceptions of quality of care, or on other proxy indicators of quality. The objective of the present study is to build on this body of literature assessing the association of the ICRMP with access and quality of care across South Africa over time. Leveraging longitudinal data now available, the effects of the programme on two measures of utilisation and six further indicators of primary care quality spanning maternal and early childhood care, TB/HIV treatment, and non-communicable disease screening are explored using panel regression models. Controlling for heterogeneity across clinics and for year, increases in ICRMP percentage scores over time appear to be associated with very small magnitude increases in childhood PHC utilisation and early usage of antenatal care. Findings, however, reveal no further significant effects on a general PHC utilisation marker nor on other proxy measures of quality included in analysis. While ICRMP percentage scores have improved over time, it appears limited impact of this improvement is evidenced in access and quality of care. Based on these findings, further research into underlying ICRMP element associations with indicators of quality of care is recommended. This may inform a revision of the ICRMP framework to better align scoring with access and PHC quality of care. To avoid the ICRMP becoming merely a tick-box exercise, targeted quality improvement plans as envisaged by the ICRMP and informed by such revised framework should be given renewed focus.